2013
DOI: 10.4103/0974-8520.123132
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑inflammatory effect of Chandrashura (Lepidium sativum Linn.) an experimental study

Abstract: Lepidium sativum Linn. (Chandrashura) of Family Cruciferae (Brassicaceae) is being used by the people of Gujarat for treating inflammatory condition like arthritis. To evaluate its anti-inflammatory activity, Charles Foster albino rats were selected and experiments were carried out in three groups, therapeutic dose group, twice of therapeutic dose group and control group. In Carrageenan-induced paw oedema, the test drug produced moderate anti-inflammatory activity; however, the effect did not show statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…The extract dose dependently attenuated CCl 4 induced rise in serum levels of AST, ALT, APT, and bilirubin suggesting its hepatoprotective activity [ 196 ]. Recently L. sativum has been shown to possess significant antioxidant [ 197 – 199 ] and anti-inflammatory [ 200 ] activities which may contribute to its hepatoprotective effect. In rats, up to 2% w/w of L. sativum in diet did not produce any toxicity, whereas 10% w/w showed mild toxicity [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extract dose dependently attenuated CCl 4 induced rise in serum levels of AST, ALT, APT, and bilirubin suggesting its hepatoprotective activity [ 196 ]. Recently L. sativum has been shown to possess significant antioxidant [ 197 – 199 ] and anti-inflammatory [ 200 ] activities which may contribute to its hepatoprotective effect. In rats, up to 2% w/w of L. sativum in diet did not produce any toxicity, whereas 10% w/w showed mild toxicity [ 201 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chemically, the seeds of L. sativum contain essential oils, fatty oils, carbohydrate, protein, fatty acids, vitamins, flavonoids and isothiocynates glycoside [4] . Experimental evidences showed that L. sativum has antihypertensive [5] , diuretic [6] , anti-asthmatic [7] , hypoglycaemic [8] , antioxidant [4] , [9] , [10] and anti-inflammatory [11] properties.…”
Section: Introductionmentioning
confidence: 99%
“…The plant leaves and seeds have been used in traditional medicine. The plant is reported to have hypoglycemic, antihypertensive, diuretic (Jouad et al, 2001;Patel et al, 2009) hemagglutinating, fracture healing (Eddouks et al, 2005;Yadav et al, 2011), anti-inflammatory (Raval et al, 2013), hepatoprotective (Abuelgasim et al, 2008;Al-Asmari et al, 2015), antioxidant (Agarwal and Verma, 2011;Zia-Ul-Haq et al, 2012) and anti-carcinogenic activities .…”
mentioning
confidence: 96%